DIFFERENTIATED INSTRUCTION TO IMPROVE STUDENTS' SKILLS IN WRITING OPINIONS ON ARGUMENTATIVE TEXT - Alin Fir Handayani; Linia S.R.R; Dedeh Rohayati; Lilis Tugiawati (ENGLISH EDUCATION STUDY PROGRAM, FACULTY OF TEACHER TRAINING AND EDUCATION, UNIVERSITAS SRIWIJAYA, 2025)
To facilitate effective learning, Differentiated Instruction-a teaching approach designed to accommodate students' diverse needs by adjusting teaching methods based on their learning styles, readiness levels, and interests-was implemented in a classroom setting. This study aims at examining the improvement of students' ability to express opinions in argumentative writing through its application. The study was conducted using classroom action research. The subject of this study were 32 students from class VIII F SMPN 2 Ciamis. The research process was divided into two cycles, consisting of preparation, action, observation, and reflection. Data were collected through pre tests and post-tests. To analyze the findings, the researcher employed a quantitative approach using mean score analysis. The research results show that Differentiated Instruction can improve students' skills in writing opinion texts. Improving students' writing skills lies in constructing sentences that comply with language rules and according to context. Additionally, students' progress was reflected in their test scores. The average score in the pre-test was 59, which increased to 67 in post-test 1 and further improved to 81 in post-test 2. These findings suggest that Differentiated Instruction can enhance students' writing skills, particularly in expressing opinions within argumentative texts.